2014
DOI: 10.14374/hfs.2014.22.2.121
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of a Serious Antibiotics-associated diarrhea Patient Treated with Modified Hyangsayukgunja-tang

Abstract: Objectives : The purpose of this study is to report a therapeutic effects of a Korean herbal prescription for antibiotics-associated diarrhea.Methods : Modified Hyangsayukgunja-tang was prescribed once or twice a day to a antibiotics-associated diarrhea patient. To observe the therapeutic effects, the frequency of defecation was counted and Bristol Stool Form Index was used. Laboratory tests were conducted periodically.Results : The frequency of defecation was decreased from 9 times a day to once a day. Accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Antibiotic-associated diarrhea (AAD) is mainly caused by alterations in the immune environment of the gut; antibiotics can break down the colonization resistance of the intestinal flora that prevents the growth of pathogens and change the content of fatty acids in the intestine or increase the amount of carbohydrates that cannot be absorbed. Furthermore, AAD is closely related to non-intestinal conditions, such as diabetes and allergies [ 3 ]. Clinical manifestations of AAD range from diarrhea with frequent loose stools to colitis, which can develop into a serious disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic-associated diarrhea (AAD) is mainly caused by alterations in the immune environment of the gut; antibiotics can break down the colonization resistance of the intestinal flora that prevents the growth of pathogens and change the content of fatty acids in the intestine or increase the amount of carbohydrates that cannot be absorbed. Furthermore, AAD is closely related to non-intestinal conditions, such as diabetes and allergies [ 3 ]. Clinical manifestations of AAD range from diarrhea with frequent loose stools to colitis, which can develop into a serious disease.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of utmost importance to identify the scale of antibiotic use, reduce indiscriminate use, and develop methods to treat side effects and alternatives to antibiotics [ 7 ]. Although several clinical trials in oriental medicine such as Hyangsayukgunja-tang have demonstrated the potential application of herbal medicines to treat AAD [ 3 , 8 ], mechanism of action and active compound of herbal medicines have not been identified yet. In the recent systematic review on traditional Chinese herbal medicine treatment for AAD, evidence of treatment efficacy for AAD is encouraging, but not conclusive because of the low methodological qualities and diversity of treatment prescriptions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%